SURGICAL STRATEGY AND TREATMENT OF POSTNECROTIC CYSTS OF PANCREAS - N. A. Bazhenova; V. A. Shornikov (Вестник хирургии имени И.И. Грекова)
The results of diagnostics and treatment were analyzed in 155 patients. Low-invasive drainage of cyst was made under control of ultrasound in 67 patients. The external drainage was carried out in 12 patients, internal drainage with cystojejunoanastomosis - in 23, cystogastroanastomosis - in 3, sleeve pancreatojejunostomy- in 6, resection of the tail of pancreas - in 2. The authors considered that it is important to have the differentiated approach to different methods of operative treatment of cysts of the pancreas according to their localization, size and degree of wall formation.